Analisis Strategi Bisnis Usaha Mikro Kecil dan Menengah (UMKM) dalam Pengembangan Usaha UD. Mete Mubaraq Lombe Kota Kendari - herlina herlina; Ninik Endang Purwati; Liwaul Liwaul (Business UHO: Jurnal Administrasi Bisnis, 2019)
This research is a qualitative descriptive study conducted at UD. Cashew Mubaraq Lome Kendari. This study aims to describe the business strategy used so that this business can develop. The business strategy includes marketing strategy, production strategy, human resources strategy, and financial strategy. The informants of this research are the Manager, Head of the Marketing Division, and the Head of the Production Division. Data were collected using interview, observation, and documentation techniques.Based on the results and research discussions obtained, it can be seen that the business strategy in marketing is to provide various types of products. Products manufactured by UD. Kendari Mubaraq Lombe Cashew and the products of 31 Small and Medium Enterprises (UKM) in Southeast Sulawesi Province. The strategy in the field of production is to pay attention to the production process properly and pay attention to the quality of raw materials, especially cashew. The strategy in the field of human resources, this business employs 15 permanent employees and 10 daily employees. Daily employees aim to facilitate the cashew production process, which is employed when producing cashew with a wholesale system. In UD financial management. Cashew Mubaraq Lombe Kendari is still simple, which records the accounting for all company revenues and expenses. In organizing the financial section is governed by the owner's wife and does not have other workers.